1986
DOI: 10.1111/j.1651-2227.1986.tb10172.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Lactose Absorption from Breast Milk during Acute Gastroenteritis

Abstract: The incidence and degree of incomplete lactose absorption was investigated in breast fed infants and children up to two years of age during acute gastroenteritis (GE). Lactose absorption was assessed in 50 patients by means of the hydrogen breath test (HBT), approximately 5.5 days after the admission to hospital. HBT detected incomplete lactose absorption of marked (lactose malabsorption) and probably mild degree in 8 and 6 patients respectively. Incomplete lactose absorption appeared to be transient in all 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A negative test was significantly bt0.05) more common in children who had diarrhoea in the week prior to testing. Previously we have shown that HBT was inappropriate to detect LM in infants with lactose intolerance (pH<6 and/or > 1/2 % reducing substances in liquid stools) from breast milk during acute gastroenteritis (11). We suggested that in most cases the low stool pH might have accounted for this, since a low colonic pH is known to reduce colonic H1 production (17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A negative test was significantly bt0.05) more common in children who had diarrhoea in the week prior to testing. Previously we have shown that HBT was inappropriate to detect LM in infants with lactose intolerance (pH<6 and/or > 1/2 % reducing substances in liquid stools) from breast milk during acute gastroenteritis (11). We suggested that in most cases the low stool pH might have accounted for this, since a low colonic pH is known to reduce colonic H1 production (17).…”
Section: Discussionmentioning
confidence: 98%
“…Because of its sensitivity HBT is considered to be procedure of choice to answer questions on lactose digestion (8). Since devices for rapid estimation of breath hydrogen have been developed (9,10) HBT also can be used under less privileged conditions (7,11).…”
mentioning
confidence: 99%